Isocitrate dehydrogenase (IDH) mutant gliomas: A Society for Neuro-Oncology (SNO) consensus review on diagnosis, management, and future directions. Issue 1 (12th October 2022) - Miller, Julie J; Gonzalez Castro, L Nicolas; McBrayer, Samuel; Weller, Michael; Cloughesy, Timothy; Portnow, Jana; Andronesi, Ovidiu; Barnholtz-Sloan, Jill S; Baumert, Brigitta G; Berger, Mitchell S; Bi, Wenya Linda; Bindra, Ranjit; et al.
Abstract: Isocitrate dehydrogenase (IDH) mutant gliomas are the most common adult, malignant primary brain tumors diagnosed in patients younger than 50, constituting an important cause of morbidity and mortality. In recent years, there has been significant progress in understanding the molecular pathogenesis and biology of these tumors, sparking multiple efforts to improve their diagnosis and treatment. In this consensus review from the Society for Neuro-Oncology (SNO), the current diagnosis and management of IDH-mutant gliomas will be discussed. In addition, novel therapies, such as targeted molecular therapies and immunotherapies, will be reviewed. Current challenges and future directions for research will be discussed.